Being Bee - Bateson, Catherine, 1960- (New York : Holiday House, 2007)
Bee faces friction at home and at school when her widowed father begins seriously dating Jazzi, who seems to take over the house and their lives, but as shared secrets and common interests finally begin to draw them together, Jazzi accidentally makes a terrible mistake.
Previously published: Australia : University of Queensland Press, 2006.
School Library Journal.
Wilson's Children.
Wilson's Junior High School.
4.4
3-6
Keywords: Families -- Juvenile fiction; Friendship -- Juvenile fiction; Guinea pigs -- Juvenile fiction; Mentally ill -- Juvenile fiction; Schools -- Juvenile fiction; Widowers -- Juvenile fiction; Family life -- Fiction; Friendship -- Fiction; Guinea pigs -- Fiction; Mentally ill -- Fiction; Schools -- Fiction; Widowers -- Fiction; Family life -- Fiction; Friendship -- Fiction; Guinea pigs -- Fiction; Mentally ill -- Fiction; School stories; Widowers -- Fiction; Australia -- Juvenile fiction; Australia -- Fiction; Australia -- Fiction